USING PICTURE BOOKS TO ENHANCE MOTIVATION AND LANGUAGE LEARNING OF REMEDIAL EFL LEARNERS - Arisa Kochiyama (University of Kuningan, 2015)
According to studies done by the Japanese Ministry of Education, Culture, Sports, Science and Technology, many secondary schools across the nation aren’t adequately preparing students to excel at college. Universities are stepping in to fill the gap by offering remedial college courses in subjects such as Japanese and English. The purpose of the present study is to explore how an EFL class for college freshmen can help the students develop the critical thinking skills as well as language skills such as pronunciation, vocabulary and grammar necessary to read at the college level.Picture books are often overlooked by adult ESL/EFL instructors as many of them feel uncomfortable reading books designed for children. However, if chosen with consideration for the interests of the students and used in ways that are appropriate for adult learners, picture books can provide valuable opportunities of language-rich experiences and interactions. In fact a number of studies in Western cultures have shown that picture books provide a wealth of possibilities for teaching English topics as well as various vocabulary sets such as family, food, clothes, and so on. They can also motivate learners to read more and learn more as the students are more likely to find reading a manageable challenge.Given these functions of picture books, the main objectives of the study are (1) to discuss the merits of using picture books in remedial English classes from the viewpoint of English language learning, (2) to investigate the effect of using picture books on the learners’ motivation and emotional development, and (3) to give a report about the students’ reactions towards an adoption of a picture book in an EFL class.Keywords: intercultural communication, English as a second language, EFL classroom, language and gender, children’s literature in EFL learning